The water-locking and cross-linking effects of graphene oxide on the load-bearing capacity of poly(vinyl alcohol) hydrogel. Issue 86 (31st August 2016) - Shi, Yan; Xiong, Dangsheng; Li, Jianliang; Wang, Nan
Abstract : The GO sheets bound part of water molecules due to the abundant oxygen-containing functional groups on its surface and impede the water infiltration between the PVA molecules, improving the water-locking ability of the PVA/GO composites. Abstract : The poor load-bearing capacity of the poly(vinyl alcohol) (PVA) hydrogel has limited its application in biomedical and orthopedic fields. In the present study, PVA/GO composite hydrogels were fabricated by the freeze–thaw method, and their mechanical and tribological properties as a function of GO content were evaluated. The results demonstrated that the GO sheets exhibited excellent interfacial interactions with the PVA hydrogel matrix. The tensile and compressive strength were improved by about 116% and 161% for the PVA/GO hydrogels with the optimized GO contents of 0.10–0.15 wt% compared to neat PVA. The GO sheets worked as the cross-linking points between the PVA molecular chains, and the individually dispersed GO sheets in the PVA matrix could maximize the filler's effect on restricting the movement of polymer chains, which was positive to the enhancement in the mechanical properties. Moreover, the water block effect of GO was thought to impede the water infiltration between the PVA molecules, which could enlarge the instantaneous pressurization under compressive load and further improve the load-bearing capacity of PVA. This was also beneficial to improving the tribological properties of PVA hydrogels.